Peningkatan Pengajaran Bahasa Inggris Untuk Kelas 5 Madrasah Ibtidaiyah Swasta (MIS) Darul Gufron Kota Batam - Megah, Suswanto Ismadi; Artanto , Tri; Maileni, Dwi Afni; Sugiharti, Sri (ASOSIASI IDEBAHASA KEPRI, 2025)
The main objective of this training is to provide a basic understanding of basic English mastery to MIS Darul Gufron Batam students. English language counseling is carried out in class 5 based on the authority of the class teacher. Through observations made by counselors to school principals and teachers, it turned out that MIS Darul Gufron Batam students had not had English lessons and they explained that English was very important to teach to their students. In connection with the implementation of these activities, this training is carried out in several techniques or ways, namely answering questions, getting to know body parts, singing English along with providing pronunciation models and exercises to participants. This training produces outcomes, namely that training participants can improve and know the basics of mastering English contextually Keywords— Improving English ability, MIS Darul Gufron .